Active learning pedagogical dimensions: discovering and bridging the pedagogical gaps - Min Hui Leow; Norshahida Hassan; Sabrina Adia Mohd Sharizal; Rafiza Abdul Razak (International Journal of Evaluation and Research in Education (IJERE), 2024)
Current literatures of active learning widely address pedagogies/approaches and their outcomes, but it does not appear to be a pedagogical consensus regarding the active learning pedagogies/approaches. This situation makes it difficult to gauge the prevalence and practicability of active learning pedagogies/approaches in specific educational levels. This systematic review is aimed to find the consensus of active learning pedagogies/approaches applied in pre-school to tertiary education on the basis of constructivist philosophy and student-centered notion, determine the desirable pedagogical dimensions, discover pedagogical gaps, and offer attention for bridging the gaps. We located seven pedagogical dimensions from teachers’ perspectives of pedagogical features, in terms of pedagogies/approaches and theories/concepts, from 148 publications that were eligible for inclusion after filtered through PRISMA. The learning outcomes or evidence of effectiveness were determined across various pedagogies/approaches in relation to pedagogical dimensions’ manifestation. Content analysis was employed in this work to encode, categorize, and develop themes. As a result, this study highlights the pedagogical gaps between desirable pedagogical dimensions’ manifestation and actual pedagogy attainment at various educational levels and provides suggestion for bridging the gaps to ensure smooth pedagogical transition. The study may serve as a foundation for future active learning pedagogical designs and enrich student-centered learning initiatives.